CD62L on blood basophils: a first pre-treatment predictor of remission in severe lupus nephritis. Issue 12 (14th December 2020) - Halfon, Matthieu; Bachelet, Delphine; Hanouna, Guillaume; Dema, Barbara; Pellefigues, Christophe; Manchon, Pauline; Laouenan, Cedric; Charles, Nicolas; Daugas, Eric
Abstract: Background: Basophils were recently shown to contribute to lupus nephritis (LN). This study assessed blood basophil activation markers (BAMs) for the diagnosis of LN severity and as pre-treatment prognostic markers of the response to treatment in patients with severe LN. Method: The diagnostic study included all the patients of a monocentric prospective observational cohort built with consecutive patients diagnosed with LN on the basis of a renal biopsy. The prognostic study selected patients of this cohort according to the following inclusion criteria: ≥18 years old, Class III or IV A ± C ± Class V or pure Class V LN at the time of inclusion and treated with an induction treatment for LN. Clinical data and BAMs were obtained at the time of the kidney biopsy. LN remission status was recorded 12 months after induction therapy initiation. Associations between baseline data and histological severity of LN or LN remission were assessed using logistic regression. Results: No significant association was found between BAMs and the histological severity of LN in 101 patients. Among the 83 patients included in the prognostic study, 64 reached renal remission. CD62L expression on blood basophils at baseline was independently negatively associated with remission at 12 months [odds ratio = 0.26, 95% confidence interval 0.08–0.82, P = 0.02 for quantitative CD62L expression >105 (geometric fluorescent intensity) gMFI]. CD62L <105 gMFI was associated with a probability of 0.87 of LN remission in the next 12 months after the start of induction therapy. Conclusion: Pre-treatment CD62L expression on blood basophils could be a first predictive biomarker of renal response to induction therapy at 12 months in patients with severe LN.